A high-throughput protocol for isolating cell-free circulating tumor DNA from peripheral blood. (29th November 2018) - Pandoh, Pawan K; Corbett, Richard D; McDonald, Helen; Alcaide, Miguel; Kirk, Heather; Trinh, Eva; Haile, Simon; MacLeod, Tina; Smailus, Duane; Bilobram, Steve; Mungall, Andrew J; Ma, Yussanne; et al.
The analysis of cell-free circulating tumor DNA (ctDNA) is potentially a less invasive, more dynamic assessment of cancer progression and treatment response than characterizing solid tumor biopsies. Standard isolation methods require separation of plasma by centrifugation, a time-consuming step that complicates automation. To address these limitations, we present an automatable magnetic bead-based ctDNA isolation method that eliminates centrifugation to purify ctDNA directly from peripheral blood (PB). To develop and test our method, ctDNA from cancer patients was purified from PB and plasma. We found that allelic fractions of somatic single-nucleotide variants from target gene capture libraries were comparable, indicating that the PB ctDNA purification method may be a suitable replacement for the plasma-based protocols currently in use.